Masthead - Editorial Collective, UnderCurrents (UnderCurrents: Journal of Critical Environmental Studies, 2014)
UnderCurrents is a collectively and student-run journal based out of the Faculty of Environmental Studies at York University. UnderCurrents explores the relations among environment, culture, and society, and publishes one thematic issue per year. All back issues are available, free of charge, on the UnderCurrents website. We are committed to publishing a variety of scholarly, creative, and activist work that critically engages with conceptions of the environment. orders & correspondence UnderCurrents c/o Faculty of Environmental Studies 277 Health Nursing and Environmental Studies Building 4700 Keele Street, York University Toronto, ON M3J 1P3 currents@yorku.ca http://www.yorku.ca/currents reviewers Michael Classens, Amanda Di Battista, Natali Downer, Oded Haas, Tania Hernández Cervantes, Aedan Hoar, Sonja Killoran-McKibbin, Dana Kandalaft, Sarah Lindsay, Andrew Mark, Michaela McMahon, Elana Santana, Madison Van West layout and design Michael Classens, Amanda Di Battista, Oded Haas, Tania Hernández Cervantes, Jonathan Kitchen, Madison Van West distribution Michael Classens, Madison Van West graduate assistants Aedan Hoar, Crystal Lamont, Madison Van West printer Incredible Printing 30 St Regis Crescent North North York, ON M3J 1Z2 T: 416-630-5200 funding support Faculty of Environmental Studies & PhD Environmental Studies Student Association special thanks to Frances Chan, Dana Craig, Ling He, Jonathan Kitchen, Dr. Catriona Sandilands, and Dr. Peter Timmerman single hard copies $10 back issues available see http://www.yorku.ca/currents for digital archive of all volumes UnderCurrents © 2014. All rights reserved. The copyright in and to the individual texts and artwork in UnderCurrents is owned by the contributors as credited. Back cover image (above) by Kayla Flinn.